2015
DOI: 10.1111/jsm.12978
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Association between Catechol-O-Methyltransferase Val158Met and Male Sexual Orientation

Abstract: Introduction Male sexual orientation is thought to have a genetic component. However, previous studies have failed to generate positive results from among candidate genes. Catechol-O-methyltransferase (COMT), located on chromosome 22, has six exons, spans 27 kb, and encodes a protein of 271 amino acids. COMT has an important role in regulating the embryonic levels of catecholamine neurotransmitters (such as dopamine, norepinephrine, and epinephrine) and estrogens. COMT is also thought to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…29 The COMT gene is located on chromosome 22q11, has 6 exons, spans 27 kb, and encodes a protein of 271 amino acids. 32 Genetic variations of the COMT gene directly affect the activity of the COMT enzyme. Furthermore, variations of the COMT gene influence the level of estrogen, resulting in changes to biologic traits related to dopamine and estrogen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 The COMT gene is located on chromosome 22q11, has 6 exons, spans 27 kb, and encodes a protein of 271 amino acids. 32 Genetic variations of the COMT gene directly affect the activity of the COMT enzyme. Furthermore, variations of the COMT gene influence the level of estrogen, resulting in changes to biologic traits related to dopamine and estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of the participants and research procedure have been described previously. 1,32 Recruitment was conducted by the Shenzhen Center for Chronic Disease Control from March 2013 to August 2015. Shenzhen Center for Chronic Disease Control is responsible for the city's prevention, treatment, and management of chronic diseases and sexually transmitted diseases.…”
Section: Recruitment Of Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports indicate that the increase in locomotor activity induced by a novel environment is indicative of the hyperactivity of the dopaminergic system in the NAcc, as proposed by Deanen et al (2003) and Alquicer et al (2004), in adult rodents. In addition, it has been reported that estrogens do not alter dopamine levels in the brain (Spencer‐Segal et al, ; Yu et al, ). Therefore, we suggest that the treatment with Prolame in aged animals probably did not improve the dopaminergic neurotransmission in the NAcc because there were no significant changes in the locomotor activity induced by a novel environment between the animals administered with this amino estrogen and the vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Исследование, проведенное в китае, указывает на связь между геном, называемым соМт, и сексуальной ориентацией [33], но расчеты свидетельствуют, что величина эффекта является слабой [32].…”
Section: по нашему мнению было бы интересно провести близнецовое исследование гетеросексуальности у меня нет никаких сомнений в том что нunclassified